Evaluation of the definition of hyperdynamic circulation in patients with cirrhosis and ascites - Cristina Ripoll; Luis Ibáñez‐Samaniego; Beatrix Neumann; Javier Vaquero; Robin Greinert; Rafael Bañares; Alexander Zipprich (Hepatology Communications, 2022)
Abstract The aim of this study was to evaluate potential criteria for defining hyperdynamic circulation in patients with cirrhosis according to the severity of ascites and its association with the activation of vasoactive systems and markers of systemic inflammation. Cross‐sectional study of patients with cirrhosis and right heart catheter measurement from two different academic centers. We evaluated systemic vascular resistance (SVR)/cardiac output (CO) according to ascites severity. The first substudy evaluated the possible definition, the second validated the findings, and the third evaluated the possible mechanisms. Comparisons were performed by means of t test, Mann–Whitney U test, and analysis of variance. Finally, linear regression curves were adjusted to evaluate the relationship between CO and SVR according to the severity of ascites and compensated or decompensated stage of cirrhosis. The study included 721 patients (substudy 1, n = 437; substudy 2, n = 197; substudy 3, n = 87). Hyperdynamic circulation (HC), defined by absolute cutoffs, had no association with the presence or severity of ascites in the first two cohorts. No association was observed between HC with renin, aldosterone, or markers of bacterial translocation. Comparison of linear regression curves showed a shift of the CO–SVR relationship to the left in patients with refractory ascites (p < 0.001) compared to patients without ascites as well as to patients with decompensated cirrhosis (p = 0.002). Conclusion: HC according to the traditional concept of high CO and low SVR is not always present in ascites. Evaluation of the CO–SVR relationship according to the severity of ascites shows a shift to the left, suggesting that the presence of HC would be defined by this shift, independent of absolute values.